Study of Breeding and Migrations of the Golden Eagle in Mongolia - Khurelsukh Dulmaa (Пернатые хищники и их охрана)
Golden Eagles (Aquila chrysaetos) play a crucial role in the ecosystems of the Bayan-Ulgii province and its neighboring regions. Our research focuses on the comprehensive survey of Golden Eagle nests and study of their migration patterns via the satellite tracking, providing valuable insights into population dynamics and migratory behaviors. In the years 2021 and 2022, we accomplished an extensive search for Golden Eagle eyries across 13 diverse counties in Bayan-Ulgii province, including Altai, Altantsugts, Bayannuur, Bayan-Ulgii, Bugat, Deluun, Erdeneburen, Nogoonnuur, Sagsai, Tolbo, Tsagaannuur, Tsengel, and Ulaankhus.